Mentoring Program: How it improves teachers ability to engage pupils in a variety of activities in kindergarten - Somariah Fitriani; Hamzah Puadi Ilyas (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
At the beginning of the learning process, class routines in the form of basic talks, songs and games are one way for kindergarten children to get used to practicing English at a young age and building their self-confidence to communicate with their friends. Thus, the aim of this study was to elaborate the mentoring activity in training teachers on how to incorporate various activities into the classroom routine. Four female teachers of an Islamic private Kindergarten participated in the mentoring program. This is a case study design of qualitative research with classroom observation and interviews. The study revealed that teachers were able to demonstrate some classroom activities through short dialogues, songs and games. It indicated that mentoring activity is found to provide participants with benefits and satisfaction, as well as the potential to motivate them to practice with kindergarten children in classroom.